(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Remote sensing is the process of detecting and identifying a region’s physical properties by assessing reflected but also transmitted radiation from a range. Analog pictures include aerial photography, whereas digital images include satellite images taken using electronic sensors. A digital picture is made up of pixels that are arranged in a two-dimensional array. Pixel-based categorization algorithms were less successful as spatial resolution increased, since the connection among pixel size as well as the dimension of observable elements on the Planet’s surface altered dramatically. In this paper the author discussed about image analysis based on objects and also characterized OBIA and GOBIA formation and its analysis. The chief objective of this paper is to gives a brief overview the technology that has been proved very efficient in analyzing the satellite (VHR) images. The study’s future scope is as follows: The globe has seen extraordinary and quick progress in the fields of remote sensing, geospatial data collecting, and mapping during the previous several decades. The technology is gaining traction in terms of its use and application in several sectors.